PENGARUH BUDAYA KERJA DAN MOTIVASI TERHADAPKINERJA PEGAWAI PADA DINAS SOSIAL PROVINSI MALUKU UTARA - Ferdi Sebe (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2015)
The purpose of this research to know how big influence Work Culture and Motivation onEmployee performance.Variables used in this study is the work culture and motivation asindependent variables, employee performance as the dependent variable. The unit of analysis is acivil servant at the Department of Social Welfare North Moluccas Province. Samples of this researchis a population of 95 (ninety five) employees. Technical analysis used is multiple linear regressionanalysis. From the results of data processing, the value= 0.05 and X144and X2= 0.598 = 0.480.From the model can be seen from the regression coefficient variable work culture (X1) of 0.598 andmotivational variables (X2) of 0.480 up one unit, then the variable employee performance (Y) will turnat 19.672 with the assumption that if not consider variables and work culture motivation of theemployee's performance will be at 19.672. To determine the relationship of free variables on thedependent variable of the correlation coefficient (R). From the table it is seen that the magnitude ofthe correlation coefficient of correlation (R) is 0.663 which shows that there is a relationship betweenthe independent variables (work culture) and (motivation) with the dependent variable (performanceof employees) in North Moluccas Provincial Social Service. The coefficient of determination (R) is0.670 which shows that the effect of work culture and motivation to employee performance by 67.0%and the remaining 33.0% is influenced by other variables not examined in this study. The resultscould be used by researchers, as a reference in subsequent studies.